Hz. Peygamber’in hanımı Ümmü Seleme - Ay, Abdurrahman (My University, 2003)
Hz. Peygamber'in Hanımı Ümmü Seleme Ümmü Seleme Mahzûmoğulları kabilesindendir. Babası Ebû Ümeyye Mekke'nin ileri gelenlerindendi. Ümmü Seleme akrabalarından Ümmü Seleme ile evlendi. O kocasıyla birlikte İslâm dinini ilk kabul edenlerdendir. Ümmü Seleme'nin Ebû Seleme'den Seleme, Ömer, Zeyneb ve Dürre adında çocukları oldu. Kocasıyla birlikte Habeşistan'a yapılan iki hicrette de bulunmuştur. O, dini uğruna birçok baskı ve eziyetlere maruz kalmıştır. Mutlu bir aile hayatı yaşayan Ümmü Seleme kocasını 626 yılında kaybetti. Resûlüllah (s.a.) dört yetimle ortada kalan bu hanımın üzüntülerini hafifletmek ve çocuklarının bakımını temin için onunla evlendi. Ümmü Seleme Resûlüllah (s.a.)'in hanımları içerisinde mühim bir yere sahiptir. Resûlüllah ile bazı savaşlara katılmıştır. Onun Hudeybiye Antlaşması'nda Hz. Peygamber'e verdiği fikir, İslâm tarihinin dönüm noktalarından biri olmuştur. Ümmü Seleme 660 yılında 84 yaşında iken Hz. Hüseyin'in şehid olma haberini duyunca vefât etti. O, Resûlüllah (s.a.)'in hanımları içerisinde en son vefât edendir. Resûlüllah (s.a.)'in eşleri içerisinde Hz. Âişe'den sonra en fazla hadis rivâyetinde bulunan Ümmü Seleme'dir. Name and Surname: Abdurrahman AY Field: Teology Programme: History of Islâm Supervisor: Prof. Dr. Mustafa FAYDA Degree Awarded and Date: Master- 11/ 06/ 2003 The Wife of the High Prophet, Ummu Salema

The Wife of the High Prophet, Ummu Salema Ummu Salema is from the tribe of Mahzum. Her father, Abu Umayyah is one of the notabilities of Meccah. Ummu Salema got married Abu Salema, one of her relatives. She is one of the first ones who accepted the Islam religion with her husband. She had children named Salema, Omar, Zainap, Durrah from Abu Salema. She had been with in the two emigrations to Abyssinia with her husband. She had been exposed to many pressures and tortures for the sake of her religion. Ummu Salema who had lived a happy family life lost her husband in 626. The messenger married this lady who had no alternative with these four children, to ease her suffers and to ensure the care of her children. Ummu Salema has an important place among the Prophet's wives. She participated in some wars with the Prophet (peace be upon him). The idea which she gave to the Prophet (peace be upon him) in Hudaibeyah Treaty had become a turning point in Islam History. She died at the age of 84 in 660 when she heard the news that High Hossayin was martyrized. She is the one who died last among the wives of the Prophet (peace be upon him). After the High Aicha, She is the one who has most related maxims from the High Prophet (peace be upon him).
Keywords: Din; Hâricîler (Hevâric); Hz. Muhammed; İslam Dini; İslam mezhepleri ve reform hareketleri; Ümmü Seleme